Environmental Impact of Long Distance Travel - Christensen, Linda; Nielsen, Otto Anker (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
This paper presents an analysis of the CO2 emission resulting from long distance travel by Danes. The emissions are analysed as the Danes’ footprint the whole way from Denmark to the final destination. International travel represents 31% of the Danes’ CO2 emission from passenger travel and the climate burden from long overseas distances is especially high even though only few travel overseas. The travel activity is furthermore increasing much more for long distances than for European destinations. Domestic travel activity with overnight stay is nearly stagnating. The study furthermore shows that the Danish development is not especially outstanding compared to other countries.